Neptune Frost and the Anthropocene: Rethinking Third Cinema’s Anticolonial Politics - Angelos Koutsourakis (Film-Philosophy)
The aim of this article is to reveal the ongoing currency of Third Cinema’s politics in view of the Anthropocene through a close reading of Saul Williams and Anisia Uzeyman’s Neptune Frost (2021). The introductory part of the article addresses the continuing relevance of Third Cinema’s politics and connects it with research interested in decolonising the Anthropocene. In the main corpus, I proceed to analyse Neptune Frost through a Third cinematic lens. I argue that the study of the film can participate in recent debates on the importance of problematising the “we” of human responsibility for the Anthropocene. 1